Orientación de la educación en el siglo XXI - Aragón Andrade, Irma (2016)
The present article addresses what skills education should consider as important in order to fulfill adequately its function. Education in the 21st Century should not be aimed at the transmission of knowledge and information but at developing the capacity to produce and use them. Different experts and international bodies  reached an agreement and pointed out that critical thinking, creativity, communication and cooperation are the essential skills to be considered in 21st Century education.